Electrical Test and Relay Protection Analysis of Power Transformer - Liang, Beibei (International Journal of Electric Power and Energy Studies, 2024)
In this paper, the electrical test and relay protection of power transformer are deeply analyzed. Firstly, the purpose, classification and common methods of electrical test are expounded, and the processing methods of test results are discussed. Then, the basic principle, device classification and configuration method of relay protection are discussed. Furthermore, the relationship between electrical test and relay protection is analyzed, and their application and significance in power transformer protection are discussed. This paper aims to provide theoretical support for improving the operation safety and reliability of power transformers.